Metabolic pathway interruption: CRISPR/Cas9-mediated knockout of tryptophan 2, 3-dioxygenase in Tribolium castaneum. (May 2018) - Adrianos, Sherry; Lorenzen, Marcé; Oppert, Brenda
Graphical abstract: Highlights: CRISPR/Cas9-mediated editing of Tribolium castaneum vermilion gene. Generation of new T. castaneum white-eyed mutant strain; vermilion ICE ( v ICE ). First report of a CRISPR-induced eye-color mutation in beetles. Abstract: The Tribolium castaneum vermilion gene encodes tryptophan 2, 3-dioxygenase, a pivotal enzyme in the ommochrome pathway that is required for proper pigmentation of the eye. A white-eyed mutant strain of T. castaneum, vermilion white ( v w ), lacks eye pigmentation due to a deletion of unknown size that removes all but the 3′-end of the vermilion gene. To create a more defined mutation in vermilion, the CRISPR/Cas9-nuclease system was used to target wild type vermilion in preblastoderm T. castaneum embryos. As adults, all injected beetles had wild type (black) eye pigmentation; however, when outcrossed to v w mates, one cross produced 19% white-eyed offspring. When the vermilion locus of these offspring was analyzed by target-site sequencing, it was determined that white-eyed individuals had a 2 bp deletion that resulted in a frame-shift mutation, presumably producing a nonfunctional enzyme. Interestingly, some of their black-eyed siblings also had a small deletion of 6 bp, but the resultant loss of two amino acids had no apparent impact on enzyme function . To establish a mutant strain homozygous for the CRISPR-induced knock-out allele, a CRISPR positive G0 male was crossed to wild type females. Their progeny were self-crossed, and white-eyed progeny were used to establish the new strain. This mutant strain is herein named vermilion ICE and will be used in future work in addition to or in place of v w .